Design and Development of a Virtual Public Complaint Service System for the Medan City Cooperatives and Small and Medium Enterprises (UKM) Service Based on a Website - Dini Maharani Wardana; Mohammad yusup; Ricky Ramadhan (INFOKUM, 2025)
Modern technology has developed rapidly, providing various solutions to facilitate activities and work. The Medan City Cooperatives and Small and Medium Enterprises (UKM) Service, which handles various complaints from the public regarding SME services, still uses manual methods in its complaint process. This manual method often causes various problems, such as delays in handling complaints and difficulties in monitoring complaint status. To overcome these problems, this study aims to design and build a website-based virtual public complaint service system application. This study uses data collection methods through observation, interviews, and documentation. In developing the application, the Personal Home Page (PHP) method is applied because of its flexibility in handling changing needs during the development process. Direct communication with clients is the main focus in this method. This application was developed using Visual Studio Code as an editor, and MySQL as a database, thus accelerating the application development process. The results of this study are in the form of a public complaint information system application that can facilitate the public and the Medan City Cooperatives and Small and Medium Enterprises Service in managing and responding to complaints effectively